2021
DOI: 10.3390/pharmacy9020097
|View full text |Cite
|
Sign up to set email alerts
|

A Methodological Assessment of Pharmacist Therapeutic Intervention Documentation (TID) in a Single Tertiary Care Hospital in Jeddah, Kingdom of Saudi Arabia

Abstract: Pharmacist intervention has valuable input to the healthcare system by reducing medication errors, costs of treatment and improving therapeutic outcomes. This study aimed to analyze pharmacists’ interventions during the verification of computerized physician order entry and to determine the association between prescribers’ level and type of prescribing errors. In this cross-sectional, observational study, data collection was carried out over three months starting from 1 January 2020 to 31 March 2020. Included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…E-prescribing has been advocated as a potential medication error reduction mechanism by studies showing lower rates of interventions [4,17]: 2.3 and 0.68%, respectively, for discharged patients. However, other studies [8] recorded a higher rate of interventions: 9.1 and 10.1%, respectively, at an inpatient pharmacy and at an emergency department for discharge prescriptions with the implementation of computerised prescribing order entry. Up to 45.1% of pharmaceutical interventions were performed on e-prescriptions in Norwegian community and hospital pharmacies [18].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…E-prescribing has been advocated as a potential medication error reduction mechanism by studies showing lower rates of interventions [4,17]: 2.3 and 0.68%, respectively, for discharged patients. However, other studies [8] recorded a higher rate of interventions: 9.1 and 10.1%, respectively, at an inpatient pharmacy and at an emergency department for discharge prescriptions with the implementation of computerised prescribing order entry. Up to 45.1% of pharmaceutical interventions were performed on e-prescriptions in Norwegian community and hospital pharmacies [18].…”
Section: Discussionmentioning
confidence: 84%
“…Studies in different health care settings have found that up to 10% of prescriptions reviewed had problems that needed pharmacists' intervention [3][4][5][6][7]. Prescription errors requiring pharmacists' interventions are usually minor errors, though a small number of prescription errors have been reported to cause major harm to patients [8,9]. A pharmacist intervention is defined as any appropriate action taken by a pharmacist to change patient management or therapy [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were descriptive, with three prospective 21,22,27 and six retrospective, 6,17,18,28,34,39,45 while one also included a survey. 17 Most of the studies were from the Middle East (Saudi Arabia, 6,17,22 Iran, 21 Lebanon 28 and Oman 18 ), two were from the United States, 27,34 one from Germany 39 and the other one from Australia. 45 For their own use, the hospitals or private health systems developed the internal documentation and/or classification systems mentioned in these studies.…”
Section: In-house Developed Documentation/ Classification Methodsmentioning
confidence: 99%
“…6,17,21,27,34,45 Others (40%) were a result of in-house modifications and adaptations of previous published studies. 18,22,28,39 The amount of information documented and the number of categories used for classifying PIs was highly variable and is detailed in Table 2.…”
Section: In-house Developed Documentation/ Classification Methodsmentioning
confidence: 99%